A Multifunctional Cascade Bioreactor Based on Hollow‐Structured Cu2MoS4 for Synergetic Cancer Chemo‐Dynamic Therapy/Starvation Therapy/Phototherapy/Immunotherapy with Remarkably Enhanced Efficacy. Issue 51 (4th November 2019) - Chang, Mengyu; Wang, Man; Wang, Meifang; Shu, Mengmeng; Ding, Binbin; Li, Chunxia; Pang, Maolin; Cui, Shuzhong; Hou, Zhiyao; Lin, Jun
Abstract: The unique tumor microenvironment (TME) facilitates cancer proliferation and metastasis, and it is hard to cure cancer completely via monotherapy. Herein, a multifunctional cascade bioreactor based on hollow mesoporous Cu2 MoS4 (CMS) loaded with glucose oxidase (GOx) is constructed for synergetic cancer therapy by chemo‐dynamic therapy (CDT)/starvation therapy/phototherapy/immunotherapy. The CMS harboring multivalent elements (Cu 1+/2+, Mo 4+/6+ ) exhibit Fenton‐like, glutathione (GSH) peroxidase‐like and catalase‐like activity. Once internalized into the tumor, CMS could generate ·OH for CDT via Fenton‐like reaction and deplete overexpressed GSH in TME to alleviate antioxidant capability of the tumors. Moreover, under hypoxia TME, the catalase‐like CMS could react with endogenous H2 O2 to generate O2 for activating the catalyzed oxidation of glucose by GOx for starvation therapy accompanied with the regeneration of H2 O2 . The regenerated H2 O2 can devote to Fenton‐like reaction for realizing GOx‐catalysis‐enhanced CDT. Meanwhile, the CMS under 1064 nm laser irradiation shows remarkable tumor‐killing ability by phototherapy due to its excellent photothermal conversion efficiency (η = 63.3%) and cytotoxic superoxide anion (·O2 − ) generation performance. More importantly, the PEGylated CMS@GOx‐based synergistic therapy combined with checkpoint blockade therapy could elicit robust immune responses for both effectively ablating primary tumors and inhibiting cancer metastasis. Abstract : A multifunctional cascade bioreactor based on hollow mesoporous Cu2 MoS4 (CMS) loaded with glucose oxidase (GOx) shows excellent Fenton‐like activity, glucose depletion ability, photothermal conversion performance, and ·O2 − generation property, and can realize chemo‐dynamic/starvation/photothermal/photodynamic therapies simultaneously. More importantly, this CMS@GOx‐based synergistic therapy combined with CTLA4 checkpoint blockade immunotherapy can elicit robust immune responses for both effectively ablating primary tumors and inhibiting cancer metastasis.